NEW Image Alberta. - Alberta College of Art Gallery, Calgary (Montreal : Lavalin Inc., 1982)
Barbier, Sally ; Ferguson, Gordon ; Giles, Wayne ; R. Meads, Arthur ; Schmid-Esler, Annemarie ; J. Spalding, Jeffrey ; Struble, Bradley ; Toogood, Wendy ; Wood, Susan
NEW Image Alberta, Alberta College of Art Gallery, Calgary, November 1982
boek